Datin Seri Rosmah officially closed 'a step to University' programme - UMP, PNC
The Association of Wives of Ministers and Deputy Ministers (BAKTI) President and wife to Prime Minister Datin Seri Rosmah Mansor officially closed 'A Step to University' programme organised by the association together with Universiti Malaysia Pahang (UMP).